Curadoria e preservação digital: um estudo sobre o Portal Brasiliana Fotográfica - Isabella Carolina Pongelupe Assis (2024)
The research is characterized by a qualitative approach, defined as an observable study for knowledge purposes, describing structure and functioning. It has a documentary approach through books, articles, websites and databases. Also, a structured analysis was carried out on the Brasiliana Fotográfico portal. Finally, interviews were conducted with the curators responsible for selecting and organizing the photographs in order to understand the curation and preservation process in this virtual environment. Furthermore, at the end, it proposes clear guidelines for the establishment of a digital preservation policy in favor of national memory. The question arises through the relationship between curation and digital preservation, in this sense, the research sought to answer: How is the process of curation and digital preservation established on the Brasiliana Fotológica portal? Based on this question, the general objective was defined as: understanding the process of curation and digital preservation on the Brasiliana Fotológica portal as a mediating mechanism for access to national memory collections. And as specific objectives: conceptualize curation and digital preservation through a bibliographic review in the field of Information Science; identify elements relevant to digital preservation, established in Brasiliana Fotográfico; highlight the digital preservation policy that guides the portal; highlight the information preservation policy characteristic of Digital Curation at the National Library and its dialogues with national memory. From a theoretical point of view, the research outlined a chronological overview of the terminology of digital curation based on the authors Beagrie (2004), Abbott (2008) and Lee and Tibbo (2011). Digital Preservation is also presented from the author Arellano (2008). Conceptualizations about heritage were highlighted, using the authors Nora (1993), Gonçalves (2009); Palma Peña (2010); Silveira and Moura (2016); Caldeira (2017), also, we chose to build a historical overview of the National Library of Brazil, in this sense, the authors Schwarcz (2002) were used; Juvêncio (2021) and Caldeira (2018). The results showed that Brasiliana Fotográfico does not have a consolidated Digital Preservation Policy and that the activity of preserving photographs is carried out individually by each of the partner institutions. It was also evidenced that some of these institutions developed their own preservation policy and others did not, thus preserving the images in the way they believe to be most effective, such as outsourcing to a partner company that provides several external HDs for storing the material.